EDITORIAL - -, - (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2020)
We started the year 2020 with “Call for Papers” for publishing our 5th edition of Assumption University-eJournal of Interdisciplinary Research (AU-eJIR). Surprisingly, in spite of the COVID-19 crisis, the response has been quite overwhelming. We received more than two dozen papers from across the world. Download the PDF to read the full message.....